Composite conversion layer, thermal neutron detector and preparation method thereof

CN123010033APending Publication Date: 2026-10-30SHENZHEN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611120419.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-27
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0008]为了解决上述技术问题,本发明提出一种复合转换层、热中子探测器及其制备方法,旨在解决现有技术中转换层只是简单地附着在探测器表面,在高温、辐照或长期使用的条件下,转换层容易剥离,导致探测器失效

Benefits of technology

[0019]有益效果,与现有技术相比,本申请提供的复合转换层由于转换材料填充并固化于多孔金属支撑层的空隙中形成互锁结构,使得其在高通量辐照条件下不发生脱落。转换层在探测器寿命周期内的可靠性是影响探测器实用化的关键因素,本发明显著改善了这一指标。另外,采用多孔金属作为支撑层,避免了因热积累引起的金刚石载流子迁移率下降及漏电流增大,提升了探测器的长期稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123010033A_ABST
    Figure CN123010033A_ABST
Patent Text Reader

Abstract

The application discloses a composite conversion layer, a thermal neutron detector and a preparation method thereof. 6 The composite conversion layer comprises a porous metal support layer and a conversion material; the porous metal support layer has a three-dimensionally connected pore structure; and the conversion material is composed of a meltable inorganic compound containing Li and is filled and solidified in the pores of the porous metal support layer. The composite conversion layer provided by the application has an interlocking structure formed by the conversion material filled and solidified in the pores of the porous metal support layer, so that the composite conversion layer does not fall off under high-flux irradiation conditions. The reliability of the conversion layer in a service life of the detector is a key factor affecting the practicality of the detector, and the application significantly improves the index. In addition, the porous metal is used as the support layer, so that the decrease of the diamond carrier mobility and the increase of the leakage current caused by heat accumulation are avoided, and the long-term stability of the detector is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of thermal neutron detector fabrication technology, and in particular to a composite conversion layer, a thermal neutron detector, and a method for fabricating the same. Background Technology

[0002] Diamond detectors possess characteristics such as a wide bandgap, high carrier mobility, strong radiation hardness, and low leakage current, resulting in outstanding detection performance under high-flux radiation environments. Diamond's bandgap is approximately 5.5 eV, a wide bandgap characteristic that minimizes thermally excited carriers at room temperature, leading to a background current several orders of magnitude lower than silicon detectors. Diamond's carrier mobility is approximately 2000 cm² / V·s, far exceeding that of silicon and silicon carbide, enabling rapid carrier collection and high-time-resolution pulse signal detection. Diamond's strong radiation hardness prevents significant radiation damage under high-flux neutron irradiation, ensuring good long-term operational stability. 6 The combination of a LiF conversion layer and a diamond detector enables high-performance thermal neutron detection.

[0003] existing 6 The LiF conversion layer is mainly prepared using the following three processes: The first method is evaporation coating. This method involves evaporation coating in a vacuum environment. 6 LiF evaporates upon heating, becoming a gaseous state. 6 LiF is deposited and condensed on the detector surface to form a thin film. The coating layer and the substrate are only physically adsorbed, without forming a strong chemical bond. Under irradiation or thermal cycling conditions, the difference in their coefficients of thermal expansion leads to interfacial stress, which can easily cause the conversion layer to detach.

[0004] The second method is cold pressing. This method will... 6 LiF powder is pressed in a mold, causing the powder particles to interlock under mechanical force, forming a sheet which is then bonded to the detector surface. Cold pressing does not require high-temperature treatment, making the process simple. However, the conversion layer lacks density and contains numerous pores. These pores reduce the effective density of the conversion layer, making it more susceptible to thermal neutrons from merging with the detector. 6 The interaction probability of Li decreases, resulting in a lower thermal neutron capture efficiency.

[0005] The third method is direct powder coating. This method will... 6 LiF powder is mixed with a binder and directly coated onto the detector surface. The binder holds the powder particles together and simultaneously attaches the conversion layer to the detector surface. Direct powder coating is simple to perform and suitable for large-area fabrication. However, the coating process suffers from poor thickness uniformity, resulting in inconsistent detection sensitivity across different areas.

[0006] Therefore, it is evident that the three processes described above share a common flaw in their bonding method between the conversion layer and the detector substrate. The conversion layer is simply attached to the detector surface, without forming an effective mechanical interlock or chemical bond between the two. Under conditions of high temperature, irradiation, or long-term use, the conversion layer is prone to peeling off, leading to detector failure.

[0007] Therefore, the existing technology still needs further development and improvement. Summary of the Invention

[0008] To address the aforementioned technical problems, this invention proposes a composite conversion layer, a thermal neutron detector, and their fabrication method. The aim is to solve the problem that in existing technologies, the conversion layer is simply attached to the detector surface, and under conditions of high temperature, irradiation, or long-term use, the conversion layer is easily peeled off, leading to detector failure. Specifically: A first aspect of this application provides a composite conversion layer, comprising: a porous metal support layer and a conversion material; the porous metal support layer having a three-dimensionally interconnected pore structure; the conversion material being composed of... 6 The material is composed of a fusible inorganic compound of Li, which fills and solidifies in the pores of the porous metal support layer.

[0009] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. The purpose and beneficial effects of the present invention can be better achieved and realized through the following preferred technical solutions.

[0010] As a preferred technical solution, in the composite conversion layer, the porous metal support layer has a thermal conductivity of not less than 50 W / m·K and a porosity of not less than 70%.

[0011] In a second aspect of this application, a thermal neutron detector is provided, comprising: a diamond detector substrate and a composite conversion layer disposed on the diamond detector substrate; the composite conversion layer is the composite conversion layer described in the first aspect.

[0012] As a preferred technical solution, the thermal neutron detector further includes a clamp that holds and fixes the composite conversion layer and the diamond detector substrate.

[0013] As a preferred technical solution, in the thermal neutron detector, the porous metal support layer has a porosity of not less than 90%, a porosity of not less than 70%, and a thickness of 0.5~2 mm.

[0014] As a preferred technical solution, in the thermal neutron detector, the porous metal support layer is one of foamed copper, foamed aluminum, foamed nickel, or woven metal mesh.

[0015] As a preferred technical solution, the thermal neutron detector, wherein the [missing information] contains 6 The fusible inorganic compounds of Li consist of two or three layers stacked along the thickness direction.

[0016] A third aspect of this application discloses a method for fabricating a thermal neutron detector as described above, comprising: will contain 6 A fusible inorganic compound of Li is placed on a porous metal support layer; Heating to above the melting point of the fusible inorganic compound allows the melt to wet and fill the pores of the porous metal support layer through capillary action; cooling and solidification form the composite conversion layer. The composite conversion layer and the diamond detector substrate are clamped and fixed using a fixture to obtain the thermal neutron detector.

[0017] As a preferred technical solution, in the preparation method, the heating is carried out under an inert atmosphere or vacuum conditions, and the heating temperature is higher than that of the product containing... 6 Melting point of fusible inorganic compounds of Li.

[0018] As a preferred technical solution, in the preparation method, the cooling rate does not exceed 3°C / min.

[0019] Beneficial effects: Compared with existing technologies, the composite conversion layer provided in this application, due to the interlocking structure formed by the conversion material filling and solidifying in the voids of the porous metal support layer, does not detach under high-flux irradiation conditions. The reliability of the conversion layer throughout the detector's lifespan is a key factor affecting the practical application of the detector, and this invention significantly improves this indicator. Furthermore, using porous metal as the support layer avoids the decrease in diamond carrier mobility and the increase in leakage current caused by heat accumulation, thus improving the long-term stability of the detector. Attached Figure Description

[0020] To more clearly illustrate the technical solutions in the embodiments of the present invention or related technologies, the drawings used in the description of the embodiments or related technologies will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0021] Figure 1 This is a schematic diagram of the composite conversion layer structure provided in an embodiment of the present invention.

[0022] Figure 2 This is a photograph of the composite conversion layer provided in an embodiment of the present invention.

[0023] Figure 3This is a partial schematic diagram of the composite conversion layer structure with clamps provided in an embodiment of the present invention.

[0024] Figure 4 This is a schematic diagram of the neutron detector structure provided in an embodiment of the present invention.

[0025] Figure 5 These are measured photos of the neutron detector detection efficiency verification provided in the embodiments of the present invention (the right side of the image shows internal details).

[0026] Figure 6 This is the measured signal of the neutron detector detection efficiency provided in the embodiments of the present invention. Detailed Implementation

[0027] The embodiments of the present invention will be described in further detail below with reference to the accompanying drawings and examples. The following examples are for illustrative purposes only and should not be construed as limiting the scope of the invention.

[0028] In the description of the embodiments of the present invention, it should be noted that the terms "center," "longitudinal," "lateral," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," and "outer," etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing the embodiments of the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on the embodiments of the present invention. In addition, the terms "first," "second," and "third" are used for descriptive purposes only and should not be construed as indicating or implying relative importance.

[0029] In the description of the embodiments of the present invention, it should be noted that, unless otherwise explicitly specified and limited, the terms "connected" and "linked" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium. Those skilled in the art can understand the specific meaning of the above terms in the embodiments of the present invention based on the specific circumstances.

[0030] In embodiments of the present invention, unless otherwise explicitly specified and limited, "above" or "below" the second feature can mean that the first feature is in direct contact with the second feature, or that the first feature is in indirect contact with the second feature through an intermediate medium. Furthermore, "above," "on top of," and "over" the second feature can mean that the first feature is directly above or diagonally above the second feature, or simply that the first feature is at a higher horizontal level than the second feature. "Below," "below," and "under" the second feature can mean that the first feature is directly below or diagonally below the second feature, or simply that the first feature is at a lower horizontal level than the second feature.

[0031] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.

[0032] like Figures 1 to 3 As shown, this application embodiment provides a composite conversion layer 10, which consists of a porous metal support layer 100 and a layer containing [a specific component] solidified in its pores. 6 It is composed of Li, a fusible inorganic compound 110. Contains... 6 Li compounds are distributed in a three-dimensional network within the pores of the porous metal. This structure differs from traditional conversion layer attachment methods. Within each pore of the porous metal, the solidified conversion material physically integrates with the three-dimensional network framework, making it difficult for the conversion material to detach from the framework. The porous metal simultaneously serves three functions: structural support, thermal conductivity, and electrical conductivity.

[0033] The equivalent thickness of the composite conversion layer 10 is determined by both the porosity of the porous metal and the amount of conversion material. By adjusting these two parameters, the equivalent thickness can be precisely controlled within the range of 10~100μm, with a thickness standard deviation of less than 2μm. It should be noted that the conversion material in the composite conversion layer 10 can be entirely melt-infiltrated and fixed in the pores of the porous metal, or it can be partially melt-infiltrated and fixed in the pores of the porous metal, and then partially located on the surface of the porous metal to form a conversion material layer.

[0034] The aforementioned composite conversion layer is applied to a thermal neutron detector. For example... Figure 4 As shown, the thermal neutron detector adopts a layered structure. From bottom to top, it consists of: a fixture base plate 20, a diamond detector substrate 30, a composite conversion layer 10, and a fixture pressure plate 40. Uniform contact pressure is applied to each part through the fixture to ensure tight adhesion between the layers. Interlayer contact is crucial for the transport efficiency of charged particles. If gaps exist at the interface, particles and tritium nuclei will lose energy when crossing the gaps, leading to a weakened detection signal. The fixture base plate 20 and the pressure plate 40 can be made of stainless steel. Stainless steel has sufficient mechanical strength and rigidity and does not deform during high-temperature sintering. Stainless steel also has a moderate coefficient of thermal expansion, providing good compatibility with diamond and copper foam.

[0035] The diamond detector substrate 30 employs a CVD diamond thin film. Diamond has a bandgap of approximately 5.5 eV, significantly higher than silicon's 1.1 eV, resulting in extremely low background current. Carrier mobility is approximately 2000 cm² / V·s, leading to fast collection speed and excellent time response characteristics. It also exhibits high radiation hardness, achieving high flux levels of up to 10... 15 Even under neutron irradiation conditions with a density of n / cm², it maintains its detection performance. These characteristics make it ideal for high-throughput neutron detection environments. The detection principle of the diamond detector is as follows: after particles and tritium nuclei enter the diamond, they ionize along the path, generating electron-hole pairs. Under a bias voltage, the electrons and holes drift towards the poles respectively, forming an induced current signal in the external circuit. Due to the high carrier mobility of diamond, the collection speed is fast, and the signal rise time is short, enabling neutron detection at high count rates.

[0036] After cleaning, a diamond thin film is deposited on both sides via magnetron sputtering to form an electrode layer. The electrode material is either titanium or gold, with a thickness of 50–200 nm. Titanium forms a titanium carbide transition layer upon contact with diamond, reducing contact resistance. Gold exhibits good chemical stability and is not easily oxidized. The magnetron sputtering process ensures a uniform electrode layer thickness and a strong bond with the diamond substrate, preventing delamination during subsequent high-temperature sintering. The electrode structure employs a sandwich layout, with the upper and lower electrodes connected to a bias power supply and a signal readout circuit, respectively, enabling carrier collection and signal extraction.

[0037] In this embodiment, a porous metal support layer is made of foamed copper. The foamed copper is selected from commercially available open-cell foamed copper with a porosity of not less than 90%, a porosity of not less than 60%, and a thickness of 0.5~2 mm, and is cut to a size that matches the effective area of ​​the diamond. The porosity affects the connectivity of the pores. The higher the porosity, the better the melting... 6 The smoother the flow of LiF in the pores, the better. When the porosity is below 90%, some pores may be closed, hindering melting. 6 LiF cannot penetrate, creating a filling dead zone. Porosity determines the fillable area. 6 The upper limit of LiF volume. When the porosity is too low. 6 Insufficient LiF filling. Excessive porosity reduces the mechanical strength of the copper foam, potentially causing deformation under clamping pressure. A porosity of 60% strikes a balance between filling capacity and mechanical strength. A thickness of 0.5–2 mm balances support strength and filling capacity. A thickness less than 0.5 mm results in insufficient support, while a thickness exceeding 2 mm increases the penetration path of charged particles, leading to greater energy loss.

[0038] Copper foam requires cleaning before use. Ultrasonically clean the copper foam with anhydrous ethanol for 15 minutes to remove the surface oxide layer and organic impurities. After cleaning, dry in a 60℃ oven for 1 hour. If the surface oxidation is severe, soak in 5% dilute hydrochloric acid for 2 minutes, then rinse thoroughly with water and dry. A clean copper foam surface facilitates melting.6 LiF wetting and adhesion. The surface oxide layer reduces wettability and affects capillary wetting.

[0039] In this embodiment, the copper foam serves two main functions in the detector. The first function is as... 6 A three-dimensional porous framework of LiF powder. During the melt sintering process, the temperature rises to... 6 After LiF reaches its melting point, solid-state... 6 LiF transforms into a liquid state. 6 LiF is drawn into the pores of the copper foam under capillary action. The magnitude of the capillary force is related to the pore size and the melt flow rate. 6 The surface tension of LiF is directly related. According to the capillary principle, the smaller the pore size, the greater the capillary force and the deeper the wetting depth. The pore size of copper foam is in the range of tens to hundreds of micrometers, which can generate sufficient capillary force to melt the copper. 6 LiF is drawn deep into the pores. This process is similar to the permeation of liquids in porous media, where melting occurs. 6 LiF advances along the interconnected pore network of the copper foam, gradually filling the entire three-dimensional framework space. After cooling and solidification, 6 LiF solidifies inside each pore of the copper foam, forming a physical interlock with the copper foam framework. This mechanical interlocking structure, unlike simple surface adhesion or bonding, ensures a strong bond between the conversion layer and the detector substrate, fundamentally solving the problem of conversion layer detachment in traditional processes.

[0040] The second function is thermal and electrical conductivity. Pure copper has a thermal conductivity of approximately 400 W / m·K, making it one of the best thermally conductive materials among commonly used metals. Under high-flux irradiation conditions, copper foam can rapidly diffuse the localized heat generated by nuclear reactions outwards, keeping the steady-state temperature rise of the conversion layer below 5°C. Without copper foam support, the temperature rise under the same flux can reach 30–50°C. This nearly one-order-of-magnitude difference demonstrates the significant improvement in heat dissipation effect brought about by porous metals. Copper foam can also be used simultaneously as the bottom electrode lead-out layer of the diamond detector substrate, eliminating the need for additional electrode layers, which helps reduce the number of interface layers and improve structural compactness. The upper surface of the copper foam is in direct contact with the conversion layer, and the lower surface is in contact with the diamond detector substrate, forming a complete electrode path and simplifying the electrical connection structure of the detector.

[0041] 6 The LiF conversion layer uses high-purity... 6 LiF powder. 6 Li isotope abundance not less than 95%, particle size less than 50 μm, and deposition rate of approximately 20–40 mg / cm³ 2Particle size affects the melting and wetting process. If the particle size is too small, the powder is prone to agglomeration and uneven distribution. If the particle size is too large, the melting time is prolonged. A particle size of less than 50 μm can achieve a balance between melting rate and uniform distribution.

[0042] 6 The thermal neutron capture nuclear reaction of LiF is as follows: 6 Li + n → α (2.05 MeV) + ³H (2.73 MeV). Total kinetic energy: 4.78 MeV. Alpha particles and tritium nuclei produce distinguishable ionization signals in diamond, with a significant energy difference, forming two independent energy peaks in the energy spectrum, demonstrating strong background detection capabilities. In contrast... 10 The nuclear reaction products of B have lower energy.

[0043] After melting and sintering, 6 LiF fully fills the pores of copper foam, achieving a density of over 90% of the theoretical density, which is superior to the 70%~80% of the evaporation process. The equivalent conversion layer thickness is adjustable within the range of 10~100μm, with a thickness standard deviation of less than 2μm.

[0044] In this embodiment, the fabrication process of the composite conversion layer is as follows. First, the composite conversion layer containing... 6 After calculating the amount of fusible inorganic compound powder of Li according to the target conversion layer thickness, it is uniformly spread on a porous metal support layer. The assembly is then heated in a protective atmosphere to above the powder's melting point. After the powder melts, the liquid conversion material, driven by capillary force, penetrates inward along the interconnected pore network of the porous metal, gradually filling the entire three-dimensional framework space. Finally, it is cooled at a controlled rate, causing the conversion material to re-solidify within the pores, forming a mechanically interlocked composite structure with the porous metal.

[0045] The following section provides a more detailed explanation of the complete fabrication process for integrating the composite conversion layer into a diamond thermal neutron detector.

[0046] The CVD diamond film was sequentially ultrasonically cleaned for 10 minutes each with acetone, ethanol, and deionized water, and then dried with nitrogen. Acetone, as an organic solvent, effectively removes grease and organic contaminants from the diamond surface. Ethanol further dissolves residual acetone and, with its better volatility, allows for rapid drying in subsequent steps. Ultrasonic cleaning with deionized water removes dissolved impurities and residual solvent. Each cleaning step, lasting 10 minutes, ensures surface cleanliness meets the requirements of subsequent processes. After cleaning, electrode layers were deposited on both sides of the diamond film using magnetron sputtering. Magnetron sputtering utilizes a magnetic field to confine plasma, allowing target atoms to deposit at high energy on the substrate surface, resulting in a film with high density and strong adhesion. Titanium or gold was selected as the electrode material, with a thickness controlled between 50 and 200 nm. Titanium exhibits good adhesion to diamond, and a titanium carbide transition layer can be formed at the interface, reducing contact resistance. Gold possesses excellent chemical stability and is not easily oxidized or reacted with during subsequent high-temperature sintering. 6The LiF reacts. The choice of electrode thickness requires a balance between electrical performance and particle transmittance. Too little thickness will result in high electrode resistivity, affecting signal transmission efficiency. Too much thickness will increase the absorption of alpha particles and tritium nuclei by the electrode layer itself, reducing the energy of charged particles reaching the diamond. A thickness range of 50–200 nm achieves a balance between conductivity and charged particle transmittance.

[0047] The working principle of the diamond detector matrix is ​​as follows: After alpha particles and tritium nuclei enter the diamond, they undergo Coulomb interactions with the diamond lattice atoms along their path of motion, exciting electrons from the valence band to the conduction band and generating electron-hole pairs. The average ionization energy required to generate one electron-hole pair in diamond is approximately 13 eV. Alpha particles have an energy of 2.05 MeV, which can generate approximately 158,000 electron-hole pairs. Tritium nuclei have an energy of 2.73 MeV, which can generate approximately 210,000 electron-hole pairs. Under an applied bias voltage, electrons and holes drift towards the positive and negative electrodes, respectively, forming an induced current signal in the external circuit. The amplitude of the induced current is proportional to the deposition energy, and the rise time is determined by the carrier drift velocity. The high carrier mobility of diamond ensures a short signal rise time and narrow pulse width, which is beneficial for pulse signal resolution under high count rate conditions. The range of alpha particles in diamond is approximately 4 μm, and the range of tritium nuclei in diamond is approximately 30 μm. The thickness of diamond films is typically selected on the order of several hundred micrometers, which is sufficient to completely block the two types of charged particles, enabling the deposition of all energy and the effective readout of signals.

[0048] Will 6 LiF powder is evenly spread onto the surface of the copper foam, ensuring that the powder covers the entire copper foam area. The spread amount is pre-calculated and determined based on the target equivalent conversion layer thickness. The assembled structure is then subjected to slight vibration for 30 seconds using a vibration table. The purpose of the vibration is to... 6 LiF powder, under gravity assistance, falls into the pore openings of the copper foam surface and distributes inward along the pore channels. The vibration frequency and amplitude need to be controlled. Excessive vibration may cause the powder to detach from the edges of the copper foam. Insufficient vibration will prevent the powder from penetrating deep into the pores, resulting in insufficient uniformity. After vibration treatment, the powder coverage reaches over 95%. Uncovered areas may experience incomplete filling after sintering, forming localized defects and affecting the uniformity of the conversion layer.

[0049] According to stainless steel base plate, foamed copper, 6 LiF powder and stainless steel pressure plates are stacked sequentially. Tighten the clamping screws to apply a clamping pressure of approximately 0.1 MPa. The stainless steel base plate and pressure plates provide rigid support, ensuring that each layer remains flat during sintering. Pressure control is crucial. Excessive pressure may crush the three-dimensional pore structure of the copper foam, disrupting capillary wetting channels, and causing… 6 LiF cannot be fully filled. Insufficient pressure results in poor contact between layers, creating gaps at the interfaces and affecting melting.6 The capillary wetting effect and continuity of the transport path of LiF are beneficial. A pressure of 0.1 MPa can prevent damage to the copper foam structure while maintaining close contact between layers. Appropriate pressure also helps maintain the relative positions of the layers during molten sintering, preventing interlayer misalignment due to differences in thermal expansion.

[0050] The assembly was placed in a tube furnace, and high-purity argon gas was introduced at a flow rate of 30 mL / min as a protective atmosphere to prevent copper oxidation at high temperatures. Argon is an inert gas and does not react with copper or... 6 LiF undergoes a chemical reaction and is suitable as a protective atmosphere. The heating program consists of two stages. The first stage involves heating from room temperature to 500°C at a rate of 5°C / min and holding at that temperature for 10 minutes. The main purpose of this stage is to remove [the harmful substances]. 6 The LiF powder adsorbs moisture and organic impurities. A heating rate of 5℃ / min is suitable. If the temperature rises too quickly, residual moisture in the powder evaporates rapidly, and the resulting steam may cause powder splattering, altering the powder distribution. 500℃ is higher than the decomposition temperature of most organic compounds; holding at this temperature for 10 minutes ensures sufficient removal of adsorbed impurities. The second stage involves heating to 880℃ at a rate of 3℃ / min and holding for 30 minutes. 6 LiF has a melting point of 848℃ under normal pressure and melts at 880℃. 6 LiF has low viscosity. Low viscosity is beneficial for liquid states. 6 Flow and infiltration of LiF in the pores of copper foam. Heat for 30 minutes to allow it to melt. 6 LiF has ample time to penetrate deep into the three-dimensional porous structure of copper foam using capillary force. A heating rate of 3℃ / min is relatively mild, allowing the temperature of both the copper foam and the diamond matrix to rise uniformly, reducing thermal stress between different parts.

[0051] Determining the sintering temperature requires balancing multiple factors. If the temperature is too low... 6 LiF did not melt sufficiently and remained in a liquid state. 6 LiF has high viscosity and poor flowability, making it unable to completely fill the tiny pores of copper foam. The oxidation rate of copper accelerates at excessively high temperatures. Even with argon protection at high temperatures, pure copper may still undergo surface oxidation due to trace amounts of oxygen in the atmosphere. Excessively high temperatures can also cause… 6 Excessive evaporation of LiF resulted in a lower-than-expected actual filler volume. (880℃ ratio) 6 LiF has a high melting point of about 32°C, which ensures full melting while preventing excessive evaporation and oxidation.

[0052] The furnace was cooled to room temperature at a rate not exceeding 3°C / min. This slow cooling was intended to prevent cracking of the conversion layer due to thermal stress. The coefficient of thermal expansion of the copper foam is approximately 17 × 10⁻⁶. -6 / K, 6 The coefficient of thermal expansion of LiF is approximately 34 × 10⁻⁶.-6 / K, the two differ by about double. During rapid cooling, the foamed copper and 6 The inconsistent shrinkage rate of LiF generates thermal stress at the interface. When this thermal stress exceeds the material's strength, microcracks may appear inside the conversion layer or at the interface. These microcracks scatter and absorb charged particles, increasing energy loss during particle escape and reducing detection efficiency. Argon gas is continuously supplied throughout the process to prevent oxidation of the high-temperature copper surface during cooling. Copper oxidizes rapidly at high temperatures, and oxidation may still occur in the initial cooling phase even as the temperature gradually decreases; therefore, a protective atmosphere must be maintained during the cooling stage.

[0053] In one implementation of this invention, a multi-layer stacked structure can be employed. Two or three composite conversion layers are sequentially fabricated on a monolithic diamond detector substrate. Each layer undergoes independent powder placement, fixture assembly, melting and sintering, and cooling steps before the next layer is fabricated. The copper foam between adjacent layers comes into contact with each other during sintering, forming an integral structure. The multi-layer structure increases the equivalent conversion layer thickness, increasing the probability of thermal neutrons being captured as they pass through more conversion material. Simultaneously, the escape path of charged particles in the multi-layer structure is lengthened, and some charged particles may be absorbed in the inner layers, resulting in a decrease in escape efficiency. Overall, the comprehensive detection efficiency of 2-3 composite conversion layers is improved compared to a single layer. This approach is suitable for high-sensitivity scenarios such as neutron flux monitoring within reactors.

[0054] In one implementation of this invention, an enrichment gradient design can be employed. Different... 6 Li enrichment 6 LiF powder is layered to create a gradient structure along the thickness direction of the conversion layer. The inner layer near the diamond detector substrate uses a high-enrichment powder. 6 LiF powder, with a low enrichment level used in the outer layer. 6 LiF powder. The inner layer is directly adjacent to diamond, and most of the charged particles generated by thermal neutron capture are closest to the detector, directly entering the detector to generate a signal. Therefore, using a highly enriched material in the inner layer maximizes detection efficiency. The outer layer is farther from diamond, and the captured charged particles need to pass through the inner layer and copper foam to reach the detector, resulting in relatively low escape efficiency. Using a low-enriched material in the outer layer reduces raw material costs while maintaining overall detection efficiency.

[0055] In one implementation of the present invention, the protective atmosphere during the sintering process can be replaced by high-purity nitrogen instead of argon. Nitrogen is also an inert gas and does not react with copper or... 6 LiF reacts. Or at 10 -3 Sintering is carried out under vacuum conditions at Pa. The advantage of vacuum sintering is that there is no residual gas in the furnace cavity, and the molten metal... 6LiF can more easily penetrate the fine pores of copper foam under vacuum, further reducing gas entrainment in the pores. Theoretically, vacuum sintering can increase the density of the conversion layer to over 95%.

[0056] In one embodiment of the present invention, a gold thin film with a thickness of 50-100 nm is pre-plated on the surface of the foamed copper to improve melting. 6 LiF wettability on copper foam. Gold and 6 The interfacial energy between LiF is low, and the liquid state... 6 LiF spreads more easily on gold surfaces. Improved wettability further enhances capillary wetting depth and uniformity. Experimental results show that pre-plating with gold reduces the standard deviation of the conversion layer thickness by approximately 10%–15%. The gold film also improves the oxidation resistance of copper foam at high temperatures and reduces oxide layer formation during sintering.

[0057] All the above embodiments are within the framework of the core inventive concept of porous metal skeleton support and molten sintering wetting, and can be selected or combined as needed. The technical features of each embodiment can overlap. For example, multilayer stacking can be combined with enrichment gradients, using different enrichment levels in each layer. 6 LiF powder. Alternatively, Au pre-plating can be combined with atmosphere substitution, and sintering of pre-plated Au-coated copper foam can be performed under vacuum conditions. All of the above combinations fall within the scope of this invention.

[0058] The porous metal material of this invention is not limited to copper foam. Aluminum foam, nickel foam, or woven metal mesh with a thermal conductivity of not less than 50 W / m·K and a porosity of not less than 70% can be used as substitutes. Aluminum foam has a thermal conductivity of approximately 200 W / m·K, and nickel foam has approximately 90 W / m·K, both of which can meet heat dissipation requirements. Woven metal mesh has regular pores, but its connectivity is not as good as that of metal foam. 6 Molten inorganic compounds of Li are not limited to 6 LiF. 6 Li₂CO₃ has a melting point of 723℃. 6 LiOH has a melting point of 462℃, and all materials can achieve equivalent functionality using the same melt-infiltration process. Materials with lower melting points require lower sintering temperatures, reducing energy consumption and the oxidation effect on copper foam. The fabrication process can also be transferred to 4H-SiC detectors, GaN detectors, or silicon detectors. 4H-SiC detectors can operate at higher temperatures. GaN detectors are sensitive to visible light, enabling neutron-photon recombination detection. Silicon detectors have the lowest cost and are suitable for large-scale applications.

[0059] Furthermore, the introduction of conversion materials is not limited to direct powder application. First, [the following is done:] 6 LiF is cold-pressed into block blanks and then placed on copper foam for melting; the core melt penetration mechanism is exactly the same. The method of cold-pressing the preforms can be predetermined.6 The dosage and shape of LiF make operation more convenient.

[0060] The fabrication process of this invention can also be applied to other detector substrates. Taking a 4H-SiC detector as an example, its bandgap is approximately 3.26 eV, allowing it to operate in high-temperature environments above 350°C. After the foamed copper composite conversion layer of this invention is fixed to the surface of the 4H-SiC detector through melt sintering, it can be used in high-temperature neutron irradiation environments such as high-temperature reactors or nuclear fuel reprocessing. Taking a GaN detector as an example, its bandgap is approximately 3.4 eV, making it sensitive to ultraviolet light and enabling the combined detection of neutrons and ultraviolet light. GaN detectors also exhibit superior radiation resistance compared to silicon detectors. While silicon detectors, although less radiation-resistant than diamond and SiC, have the lowest cost and the most mature fabrication process, their application in silicon detectors can significantly reduce the manufacturing cost of thermal neutron detectors. Given the large market size for silicon detectors, this technological combination facilitates the widespread application of this invention.

[0061] The difference in the detector substrate material mainly affects the bias conditions and the design of the signal readout circuit. Wide bandgap semiconductors such as diamond and SiC require higher bias voltages to achieve complete depletion, but have lower leakage current. Silicon detectors have lower bias voltage requirements, and the design of the signal readout circuit is more mature. Regardless of the substrate material used, the foamed copper composite conversion layer structure and melt sintering process of this invention are applicable.

[0062] In terms of detector packaging, the sintered composite conversion layer and diamond detector substrate can be integrally packaged using a fixture. The package uses a metal or ceramic shell, internally filled with inert gas for protection. Electrical signal output interfaces are provided on the package shell for connecting the bias power supply and signal readout circuitry. The main purpose of the packaging is to isolate moisture and contaminants from the external environment, protecting the conversion layer and the diamond detector substrate. After packaging, the detector can be used under a wider range of operating conditions, including high humidity, high temperature, or strong vibration environments.

[0063] The core design concept of this invention is to use a highly thermally conductive porous metal framework to support the molten conversion material, which is then cured through capillary penetration to form a composite conversion layer. This design concept can be extended to combinations of various materials and application scenarios.

[0064] In the field of nuclear monitoring, this solution can be applied... 6 LiF can be converted into a conversion material enriched with other nuclides for detecting different types of neutrons or charged particles. For example, replacing the conversion material with... 10 Boride-enriched borates can be used as an alternative detection scheme for thermal neutrons. The conversion material is replaced with... 235 U or 239Fluorides of Pu can be used for fast neutron fission detection. The process flow of the above scheme is the same as that of this scheme, only the sintering temperature needs to be adjusted to match the melting point of the conversion material.

[0065] In the field of space exploration, the high radiation hardness of diamond detectors and the heat dissipation capabilities of porous metals make this solution suitable for use in the space environment. In space, there is no convection cooling; thermal management primarily relies on thermal conduction and radiation. The high thermal conductivity of the porous metal conducts heat from the conversion layer to the detector shell, which is then dissipated through thermal radiation, solving the thermal management challenges in space. The radiation resistance of diamond detectors in the space radiation environment has also been widely verified. Combined with the composite conversion layer of this invention, long-term monitoring of the neutron radiation environment in space can be achieved.

[0066] Finally, it should be noted that the above embodiments are only for illustrating the present invention and not for limiting the present invention. Although the present invention has been described in detail with reference to the embodiments, those skilled in the art should understand that various combinations, modifications, or equivalent substitutions of the technical solutions of the present invention do not depart from the spirit and scope of the technical solutions of the present invention and should be covered within the scope of the claims of the present invention.

Claims

1. A composite conversion layer, characterized in that, include: A porous metal support layer and a conversion material; the porous metal support layer has a three-dimensional interconnected pore structure; the conversion material is composed of... 6 The material is composed of a fusible inorganic compound of Li, which fills and solidifies in the pores of the porous metal support layer.

2. The composite conversion layer according to claim 1, characterized in that, The porous metal support layer has a thermal conductivity of not less than 50 W / m·K and a porosity of not less than 70%.

3. A thermal neutron detector, characterized in that, include: A diamond detector substrate and a composite conversion layer disposed on the diamond detector substrate; the composite conversion layer is the composite conversion layer as described in claim 1.

4. The thermal neutron detector according to claim 3, characterized in that, It also includes a clamp that holds and fixes the composite conversion layer and the diamond detector substrate.

5. The thermal neutron detector according to claim 3, characterized in that, The porous metal support layer has a porosity of not less than 90%, a porosity of not less than 70%, and a thickness of 0.5~2 mm.

6. The thermal neutron detector according to claim 3, characterized in that, The porous metal support layer is one of foamed copper, foamed aluminum, foamed nickel, or woven metal mesh.

7. The thermal neutron detector according to claim 3, characterized in that, The containing 6 The fusible inorganic compounds of Li consist of two or three layers stacked along the thickness direction.

8. A method for fabricating a thermal neutron detector as described in claim 3, characterized in that, include: will contain 6 A fusible inorganic compound of Li is placed on a porous metal support layer; Heating to above the melting point of the fusible inorganic compound allows the melt to wet and fill the pores of the porous metal support layer through capillary action. Cooling and solidification form the composite conversion layer; The composite conversion layer and the diamond detector substrate are clamped and fixed using a fixture to obtain the thermal neutron detector.

9. The preparation method according to claim 8, characterized in that, The heating is carried out under an inert atmosphere or vacuum, and the heating temperature is higher than that of the substance containing... 6 Melting point of fusible inorganic compounds of Li.

10. The preparation method according to claim 8, characterized in that, The cooling rate does not exceed 3°C / min.